Multimodal pedagogies and access to higher education - Archer, Arlene (South African Journal of Higher Education, 2016)
This paper focuses on academic literacies and access to Higher Education in South Africa. Specifically, it explores the ways in which multimodal pedagogies can enable recognition of a diversity of student resources, whilst at the same time enabling access to dominant practices. Formal education often closes down access to a range of semiotic resources and multimodal pedagogies could potentially recover recognition of these. Recognition is about noticing resources in terms of some existing framework, utilising them in a range of contexts, and valuing them in terms of assessment. This paper highlights the relations between multimodal pedagogies, academic literacies and access to Higher Education. The importance of writing is acknowledged and ways of using multimodal resources to access writing discussed, including interrogating metaphorical objects, oral performance and multimodal citation.